2011
DOI: 10.28945/1354
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Doctorate: Is Doctoral Research that Studies the Emotional Labor of Doctoral Students Possible?

Abstract: This paper addresses the emotional labor of qualitative researchers in the social sciences, in general, and of doctoral students in the social sciences whose research is conducted using the qualitative research paradigm, in particular. The first part of this paper presents a brief review of the literature on the emotional labor of researchers in the social sciences. The second part of this paper discusses a doctoral research that investigates the emotional labor of doctoral students, examining two questions: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Engaged doctoral students have been found to experience high levels of energy, to find their research work meaningful (Virtanen & Pyhältö, in press), and to remain more persistent when they encounter problems during their doctoral journeys than students who suffer from disengagement in their doctoral studies (Tuomainen, Pyhältö, & Lonka, 2012). Nutov and Hazzan (2011) have suggested that the doctoral process is an intensive, emotionally loaded, depleting, and inspiring process, during which the doctoral students experience a wide range of situations and emotions that may promote or decrease their engagement in their doctoral studies. The quality and quantity of student-faculty interaction, especially the supervisory relationship, has been shown to be one of the central regulators of doctoral student engagement (Knowles, 1999;Mainhard, van der Rijst, van Tartwijk, & Wubbels, 2009;Seagram, Gould, & Pyke, 1998).…”
Section: Engagement In Doctoral Researchmentioning
confidence: 99%
“…Engaged doctoral students have been found to experience high levels of energy, to find their research work meaningful (Virtanen & Pyhältö, in press), and to remain more persistent when they encounter problems during their doctoral journeys than students who suffer from disengagement in their doctoral studies (Tuomainen, Pyhältö, & Lonka, 2012). Nutov and Hazzan (2011) have suggested that the doctoral process is an intensive, emotionally loaded, depleting, and inspiring process, during which the doctoral students experience a wide range of situations and emotions that may promote or decrease their engagement in their doctoral studies. The quality and quantity of student-faculty interaction, especially the supervisory relationship, has been shown to be one of the central regulators of doctoral student engagement (Knowles, 1999;Mainhard, van der Rijst, van Tartwijk, & Wubbels, 2009;Seagram, Gould, & Pyke, 1998).…”
Section: Engagement In Doctoral Researchmentioning
confidence: 99%
“…There are a number of considerations a student takes into account, foremost being academic reputation, knowledge, common interest, personality, and time commitment among other criteria (Liechty et al, 2009;Nutov & Hazzan, 2011;Ray, 2007). However, if choice of supervisor is based solely on these criteria and does not account for paradigmatic alignment or methodological expertise, this can be problematic for the doctoral student choosing ConGT.…”
Section: Selection Of Supervisor(s) and Committeementioning
confidence: 99%
“…While expertise in substantive area, knowledge of research methods, and interpersonal connection are critical in successful mentoring of any PhD student (Nutov & Hazzan, 2011;Walker, Golde, Jones, Bueschel, & Hutchings, 2008), use of ConGT requires an appreciation of, and support for, a constructivist perspective in relation to GT methodology. Since our personal goal was to be faithful to the tenets of ConGT, a view of ConGT as a methodology and not merely an analytical framework would have been ideal in supporting our methodological development.…”
Section: Selection Of Supervisor(s) and Committeementioning
confidence: 99%
“…In fact, Bledsoe et al (2007, p. 614), describing changes in IRB structure at their university since the 1990s, comment that the time frame for review increased: 'from usually around forty-eight hours for social science reviews to what could be months for even the most routine projects'. In this instance, it added pressure to the already challenging process of undertaking graduate research (Nutov & Hazzan, 2011;Spaulding & Rockinson-Szapkiw, 2012).…”
Section: Ethics Approval Processmentioning
confidence: 99%